Case report of a large cephalic vein aneurysm inducing heart failure in a renal transplant patient with radio-cephalic fistula for haemodialysis. (2020) - Panagrosso, Marco; Bracale, Umberto Marcello; del Guercio, Luca; Viscardi, Alessia; Peluso, Antonio; Dinoto, Ettore
Highlights: The venous aneurysm is one of the most common complications of autologous AVF. The vein aneurysm should be treat by surgical resection and anastomotic ligature. AVF shouldn't be ligated from 1-year kidney transplantation except in some cases. Surgical ligation to prevent complications could be considered an option. Abstract: Introduction: The autologous arteriovenous fistula (AVF) is considered the best vascular access for haemodialysis in patients with chronic kidney disease but in time can lead to several complications. Presentation of a case: Herein we describe a case of a large cephalic vein aneurysm causing heart failure in a renal transplant patient being treated with radio-cephalic AVF for haemodialysis. The patient was judged to be at very high risk for potential catastrophic rupture of the aneurysm and his cardiac function was deteriorating so a surgical resection was offered. Under general anesthesia, a longitudinal incision was performed on the volar side of the forearm and the anastomotic junction was ligated. The cephalic vein aneurysm was isolated and a total resection of the vein, up to the joint of the elbow, was carried out. A specimen was also submitted for histological and immunohistochemical analysis. Discussion: At present no clear indications pertaining to the need to close an AVF after kidney transplantation exist. Some authors recommend a closing of the fistula in patients with stable renal function to prevent the onset of complications, while others advise never to close the asymptomatic fistula in order to preserve vascular access for haemodialysis in case of graft failure. Conclusion: Based on our clinical experience, we suggest not ligating vascular access during the first year following transplantation with the exception of patients needing emergent closure. Otherwise, surgical closure to prevent the onset of complications could be considered a viable option in the following subset of patients: those who are 3 or more years from transplantation with good and stable renal function, those with a significant growth of venous aneurysms or have a high AVF flow rate or are young patients.